SAT-473 Thyroid Dysfunction in a Patient with Malignant Melanoma Treated with Immune Checkpoint Blockade - Gupta, Shaveta (J Endocr Soc, 2020)
Thyroid Dysfunction in a Patient with Malignant Melanoma Treated with Immune Checkpoint Blockade Background: Thyroid dysfunction is a known immune-related adverse event associated with immune checkpoint inhibitor therapy. Clinical Case: 48 year old female, newly diagnosed with metastatic melanoma started on combination immune checkpoint inhibitor therapy with Ipilimumab and Nivolumab. Her baseline thyroid function tests were normal. 6 weeks after the first cycle, she was found to have TSH of 0.010IU/ml with FT4 3.33IU/ml. Patient was started on Prednisone for 2 weeks and beta-blocker for symptom control by oncology team and referred to endocrine clinic for further evaluation. She was diagnosed with thyroiditis. TSI and thyroid uptake scan were not checked as there was no clinical suspicion for Graves disease in the absence of ophthalmopathy and thyroid enlargement. Serial TFTs were obtained which showed improvement. However, 4 weeks later, patient developed overt hypothyroidism (TSH 11.800IU/ml, FT4 0.68IU/ml) for which therapy with levothyroxine was started. Conclusion: Our case emphasizes the importance of close monitoring of patients receiving Immune Checkpoint Inhibitor Therapy for prompt diagnosis and management of the thyroid disorders to prevent complications such as thyroid storm or myxedema coma. Per the ASCO guidelines, Brahmer et al recommends monitoring TFTs every 4 to 6 weeks from the start of the therapy and every 2-3 weeks after the diagnosis to detect conversion of thyroiditis and hyperthyroidism to hypothyroidism. In the combination therapy, the median time to onset of hyperthyroidism and hypothyroidism after first treatment was 21 and 63 days and transition time from hyperthyroidism to hypothyroidism was 42 days. Reference: (1) Characterization of Thyroid Disorders in Patients Receiving Immune Checkpoint Inhibition Therapy Lee et al (2) Management of Immune-Related Adverse Events in Patients Treated With Immune Checkpoint Inhibitor Therapy: American Society of Clinical Oncology Clinical Practice Guideline Julie R. Brahmer et al